Respuesta :
Hi there!
»»————- ★ ————-««
I believe your answer is:
[tex]x = 1[/tex]
»»————- ★ ————-««
Here’s why:
⸻⸻⸻⸻
[tex]\boxed{\text{Calculating the answer...}}\\\\\frac{x+3}{6}=\frac{2}{3}\\\----------\\\rightarrow (\frac{x+3}{6})6=(\frac{2}{3})6\\\\\rightarrow x + 3 = 4\\\\\rightarrow x + 3 - 3 = 4 - 3\\\\\rightarrow \boxed{x=1}[/tex]
⸻⸻⸻⸻
»»————- ★ ————-««
Hope this helps you. I apologize if it’s incorrect.
Answer:
x = 1
Step-by-step explanation:
( x + 3 ) / 6 = 2 / 3
Step 1 Cross multiply
( x + 3 ) * 3 = 3x + 9
2 * 6 = 12
We now have 3x + 9 = 12
Step 2 Subtract 9 from both sides
3x + 9 - 9 = 12 - 9
9 - 9 cancels out
12 - 9 = 3
We now have 3x = 3
Final step; divide both sides by 3
3x/3 = x
3/3 = 1
We're left with x = 1
To check our answer we can plug in 1 for x in the expression
( x + 3 ) / 6 = 2 / 3
Substitute 1 for x
1 + 3 / 6 = 2 / 3
Simplify addition
4/6 = 2/3
Simplify fraction
2/3 = 2/3 ✓